Malagasy spittlebugs (Hemiptera: Cercopidae), a taxonomic review of genera from Madagascar - Bucher, Manon; Bouteille, Émilien; Le Cesne, Maxime (European Journal of Taxonomy, 2024)
The nine genera of Malagasy spittlebug are revised, with the addition of new characters, facilitating the identification of the species. Nesaulax Jacobi, 1917, is synonymized with Amberana Distant, 1908, leading to a new combination for Amberana vittipennis (Bergroth, 1894). A new endemic genus Soulierana Bucher & Bouteille gen. nov. is proposed for two species originally placed in Literna Stål, 1866, based on morphological characters of the head, tegmina and male genitalia. Also, three new species are described in this genus: Soulierana bigidea Bucher gen. et sp. nov., Soulierana claudinae Bouteille gen. et sp. nov. and Soulierana kelymena Le Cesne gen. et sp. nov. Pictures of species and drawings of the male genitalia for all genera, with the exception of Rhinaulax Amyot & Serville, 1843, Alluaudensia Lallemand, 1920 and Literna, are included. An identification key is available in both a dichotomous format and an interactive format (Xper3).